Formirovanie metodiki podgotovki borcov greko-rimskogo stilja v novych uslovijach sorevnovatel'noj dejatel'nosti - Akopjan, A. O.; Pankov, V. O.; Kim, A. Ju. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
the Radical changes of the rules of competitions in the Grecian-Roman wrestling have made completely new demands to the technique of elite wrestlers training, which have touched basically the conditions of the effective realization of the technical actions.